KONSTRUKSI HUKUM PENGATURAN BANK TANAH UNTUK MEWUJUDKAN PENGELOLAAN ASET TANAH NEGARA BERKEADILAN - Fatimah Al Zahra (Arena Hukum, 2017)
AbstractThe amount of land that remains is not proportional to the needs of the physical development of land for growing along with the increasing population. This condition resulted in the incidence of social conflict. Communities tend to be unwilling to let go of land that it owns for infrastructure development under the pretext of price set by the Government is too low. Land Bank can be one alternative procurement ground nirkonflik that can be applied to overcome the crisis in infrastructure development. By using the methods of normative legal research, this research aims to analyze the concept of a land bank with the statute approach, a conceptual approach, and comparative approach. With the summary that the construction of the law setting the land bank as an attempt to realize the asset management within State land can be achieved by establishing rules concerning the level land bank legislation. The values of Justice, legal certainty and legal expediency in organizing land bank should be included in the basis and legal norms on the charge of draft legislation that will be compiled.Â AbstrakJumlah tanah yang tetap tidak sebanding dengan kebutuhan tanah untuk pembangunan fisik yang terus meningkat seiring dengan bertambahnya jumlah penduduk. Kondisi ini mengakibatkan timbulnya konflik sosial. Masyarakat cenderung tidak mau melepaskan tanah yang dimilikinya untuk pembangunan infrastruktur dengan dalih harga yang ditetapkan oleh pemerintah terlalu rendah. Bank tanah dapat menjadi salah satu alternatif pengadaan tanah nirkonflik yang dapat diterapkan untuk mengatasi krisis tanah dalam pembangunan infrastruktur. Dengan menggunakan metode penelitian hukum normatif, penelitian ini bertujuan untuk menganalisis konsep bank tanah dengan pendekatan peraturan perundang-undangan (statute approach), pendekatan konseptual (conceptual approach), dan pendekatan perbandingan (comparative approach). Dengan simpulan bahwa konstruksi hukum pengaturan bank tanah sebagai upaya untuk mewujudkan pengelolaan aset tanah negara berkeadilan dapat tercapai dengan membentuk aturan mengenai bank tanah yang setingkat undang-undang. Nilai-nilai keadilan, kepastian hukum dan kemanfaatan hukum dalam penyelenggaraan bank tanah harus dimasukkan dalam asas dan norma hukum pada muatan rancangan undang-undang yang akan disusun.